Improving the prediction of potato yield gaps: Solanum-model parameterization and evaluation in southwestern China. - Ying Wang; Muhammad Abdul Rehman Rashid; Shumin Liang; Zulfiqar Ali Sahito; Ju Yang; Zhou Li; Zuo Hu; Zhechao Pan; Qijun Sui (PLoS ONE)
Sustainable agriculture has made significant contributions to both food security and global economic growth. Development of new cultivars and identifying and utilizing the yield potential of existing gemplasms are two key options for sustainable crop production. In this study, field trials and a new plant growth stimulator model developed by the International Potato Center called "Solanum" was used to assess the yield potential and 'yield gaps' of three potato cultivars in spring, autumn, and early spring seasons in southwestern China. The results showed that the average potential yield of potato crops in spring, early spring, and autumn seasons was 125.6 t/ha, 56.40 t/ha, and 45.30 t/ha with a gap from the potential yield of 107.30 t/ha, 36.70 t/ha, and 32.10t/ha, respectively. Further analysis revealed that the late blight disease was the main cause of large yield gap in spring season, whereas inadequate rain fall was the the major factor impacting the actual yield of potato crops in autumn and early spring seasons. Therefore, we report for the first time, that the spring potato in Yunnan Province, southwestern China has the highest potential yield in the world, and that extending growing season coupled with managing late blight can increase actual yield by 115%. The high yield potential of spring potato could be very beneficial to the local economy and add an enormous pelf and prosperity to the region.